Morphology and characteristics of eight Oxisols in contrasting landscapes of Costa Rica - Camacho Umaña, Manuel Ernesto (2021)
Oxisols have been previously reported in Costa Rica. However, few studies provided specific data to corroborate their presence and explain their genesis under different soil-forming factors. This study was performed with the aim to confirm Oxisols occurrence in different landscapes and parent materials in Costa Rica. Eight pedons were sampled, described, characterized, and classified according to Soil Taxonomy in five landscapes. All pedons studied presented clay contents above 40% in surface horizons. Subsurface horizons presented red colors, high contents of low-activity clay minerals with cation exchange capacity values at pH 7 (CEC7) less than 16 cmolc kg−1 clay and less than 9.6% weatherable minerals in the sand fraction. The suborders Ustox, Udox and Perox were identified. Among the Ustox, three contrasting subgroups were identified: Kandiustalfic Eustrustox, Plinthic Kandiustox, and Anionic Acrustox. Conversely, soils classified into the suborder Udox presented the same great group: Kandiudox; with three subgroups identified: Typic Kandiudox, Plinthic Kandiudox, and Rhodic Kandiudox. In addition, one pedon was classified into the suborder Perox, with the subgroup Andic Haploperox. The diversity in geologic materials (basaltic, pyroclastic, and sedimentary rocks), geomorphology (mountains, plains, dissected volcanic cones, and Quaternary alluvial fans), and the climatic conditions (total annual rainfall ranged from 1853 to 5780 mm year−1) observed in the studied areas made possible the diverse taxonomic classification for the eight Oxisols. Results obtained confirmed occurrence of Oxisols in Costa Rica and verify soil classification from previous literature reports. Our findings in soil genesis and forming factors enhance the knowledge in pedogenesis and properties of advanced weathering stage soils in Central America.